Representasi Feminitas dan Kekuasaan Dalam Film Wicked: Analisis Semiotika - Prulicia Maharani Nitami; Wulan Purnama Sari (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
This study analyzes the representation of femininity and the construction of women's power in Wicked: Part One (2024) using Roland Barthes' semiotic approach through three levels of meaning: denotation, connotation, and myth. The analysis aims to uncover how visual, narrative, and symbolic signs in the film work to construct meanings surrounding the two main characters, Glinda and Elphaba. The findings reveal a strong contrast between the ideal femininity represented by Glinda, who aligns with social norms and dominant aesthetics, and Elphaba’s position as 'the Other,' marked by physical differences and social stigma. This distinction serves not only as an aesthetic element but also as an ideological code exposing the power structure within the fictional society of Oz. The study also finds that the film presents two distinct modes of female power. Glinda exhibits power based on performativity, social acceptance, and patriarchal negotiation, whereas Elphaba demonstrates power through resistance, defiance, and efforts to subvert the stigma attached to her. These representations deconstruct the myth that obedience is the only way for women to be accepted within the social structure. Consequently, Wicked: Part One presents a counter-discourse asserting that femininity and women's power are complex, fluid, and intrinsically linked to the power relations that construct who is deemed